Reproductive ecology, spawning potential, and breeding season of blue swimming crab (Portunidae: Portunus pelagicus) in Java Sea, Indonesia - TRI ERNAWATI; BAMBANG SUMIONO; HAWIS MADDUPPA (Biodiversitas Journal of Biological Diversity, 2017)
Ernawati T, Sumiono B, Madduppa H. 2017. Reproductive ecology, spawning potential, and breeding season of blue swimming crab (Portunidae: Portunus pelagicus) in Java Sea, Indonesia. Biodiversitas 18: 1705-1713. The blue swimming crab (Portunidae: Portunus pelagicus) is one of the most economically important fisheries species in Indonesia. Little is known about their reproductive ecology and key biological characteristics. This study aimed to investigate population biology and reproductive ecology (Carapace’s width to weight relationship, growth, natural mortality, size at first maturity and at first captured, Spawning Potential Ratio (SPR), and breeding season) of P. pelagicus at six important landing sites around the Java Sea (Jakarta, Cirebon, Demak, Rembang, Sumenep, and Sampit) from January 2014 to January 2015. Monthly data were collected by fishers at each landing sites, with a total of 14,408 individuals being measured. The study found that males were heavier than females and the smallest mean of individuals’ height belonged to Jakarta compared to other locations. The growth parameters varied at the different locations. Crabs could grow up to 100 mm in 10 months with the maximum age being less than three years. The growth rate (K) of more than 1 indicated a fast-growing crustacean with a short lifespan. The lowest carapace width at first capture (Lc) for the BSC was obtained from crabs caught using a bottom gillnet landed in Jakarta, followed by dredged crabs in Cirebon. The mean carapace width at first maturity (Lm) in the Java Sea was 10.6 cm, with the lowest Lm of female crabs being landed in Cirebon and the highest in Sampit. The Spawning Potential Ratio (SPR) ranged from 11% to 24% and the selectivity curve for the BSC fishery at each landing sites is positioned well to the right of the generic maturity curve, except in Demak, suggests that the operation enables almost all crabs to mature and spawn before entering the fishery. The collapsible trap was the most selective gear, with an average catch of 112 mm across at all landing sites, and the least selective was in trawls. Therefore consideration needs to be given to the different gear types used to catch crabs to leave smaller crabs in the water longer to grow to maturity. Considering its fast growth and peak season (February-April and August-October), a short-period is recommended at some sites that have been over-exploited to rebuild a broodstock to support the long-term sustainability of this species.